Organ preservation after total neoadjuvant therapy for locally advanced rectal cancer (CAO/ARO/AIO-16): an open-label, multicentre, single-arm, phase 2 trial - Gani, Cihan; Fokas, Emmanouil; Polat, Bülent; Ott, Oliver J; Diefenhardt, Markus; Königsrainer, Alfred; Böke, Simon; Kirschniak, Andreas; Bachmann, Robert; Wichmann, Dörte; Bitzer, Michael; Clasen, Stephan; et al. (The lancet. Gastroenterology & Hepatology, 2025)
Background - Total neoadjuvant therapy has been shown to increase pathological complete response and disease-free survival in patients with locally advanced rectal cancer after total mesorectal excision (TME). We hypothesised that total neoadjuvant therapy could maximise the number of patients attaining a clinical complete response who could then be instead referred to organ preservation with watch and wait. - Methods - This open-label, multicentre, single-arm, phase 2 study (CAO/ARO/AIO-16) was conducted at four centres across Germany. Patients aged 18 years or older with histologically confirmed cT1-2N1-2 or cT3a-dN0/N1-2 rectal adenocarcinoma up to 12 cm from the anal verge and without distant metastases received chemoradiotherapy. Radiotherapy was administered in daily fractions of 1·8 Gy, 5 days per week, starting at day 1 and ending at day 38, for a total of 28 fractions and total dose of 50·4 Gy. Concomitant fluorouracil (250 mg/m2 per day as a continuous venous infusion from day 1 to day 14 and day 22 to day 35) and oxaliplatin (50 mg/m2 intravenously on days 1, 8, 22, and 29) were administered. Chemoradiotherapy was followed by three cycles of consolidation FOLFOX (fluorouracil [2400 mg/m2 over 46 h by continuous venous infusion], oxaliplatin [100 mg/m2 intravenously as a 2-h infusion], and leucovorin [400 mg/m2 intravenously as a 2-h infusion]) starting on days 57, 71, and 85. Response assessment was scheduled on day 106 after the start of total neoadjuvant therapy and included digital rectal examination, rectoscopy, and pelvic MRI. In case of a clinical complete response, patients were scheduled for a watch and wait surveillance protocol. Patients with a near clinical complete response on day 106 were offered a second assessment on day 196. In case of conversion to a clinical complete response on this repeated assessment, the same watch and wait surveillance protocol was initiated. Alternatively, local excision was considered on day 196 if technically feasible. In all other cases, immediate TME surgery was recommended. The primary endpoint was the clinical complete response rate on day 106 or 196 assessed in patients who started chemoradiotherapy (intention-to-treat population). Toxicity was also assessed in this patient population. The study was registered with ClinicalTrials.gov (NCT03561142) and is complete. - Findings - Between June 1, 2018, and Oct 7, 2020, we enrolled 93 patients, of whom 91 (mean age 61 years [SD 10]; 61 [67%] men and 30 [33%] women) started chemoradiotherapy, 88 started consolidation chemotherapy, and 88 had a response assessment on day 106. At this first assessment, 13 (15%) patients were classified as having a clinical complete response and were assigned to watch and wait, 33 (38%) met criteria for a near clinical complete response and were scheduled for reassessment, and 42 (48%) had a poor response and were referred for immediate TME. At the second assessment, on day 196, 21 (64%) of 33 patients converted to a clinical complete response, two underwent local excision with a pathological complete response (and were also assigned to watch and wait), and ten had TME. Therefore, for the primary endpoint, 34 (37%) of the initial 91 patients attained a clinical complete response after total neoadjuvant therapy. Overall, 33 (36%) of 91 patients developed grade 3 or 4 toxicity during total neoadjuvant therapy. 17 (19%) patients developed grade 3 toxicity during chemoradiotherapy, with no grade 4-5 toxicity occurring at this treatment stage. The most frequently reported grade 3 toxicities during chemoradiotherapy were diarrhoea in nine (10%) patients and infections in six (7%). During consolidation chemotherapy, 17 (19%) of 88 patients had grade 3 toxicities, the most common of which were leucopenia (in seven [8%] patients) and neutropenia (in seven [8%]). One (1%) patient had grade 4 neutropenia and one patient died of COVID-19-associated pneumonia. Grade 3 and grade 4 adverse events during follow-up were recorded in 19 (21%) of 91 patients. - Interpretation - Upfront chemoradiotherapy and three cycles of consolidation FOLFOX result in a high rate of clinical complete response with an acceptable toxicity profile. Total neoadjuvant therapy combined with a watch and wait approach after a clinical complete response can be considered for patients with locally advanced rectal cancer seeking an alternative to TME surgery. - Funding - Medical Faculty Tübingen.